A thin mantle transition zone beneath the equatorial Mid-Atlantic Ridge - Agius, M; Rychert, K; Harmon, N; Tharimina, S; Kendall, J (Springer Nature, 2021)
The location and degree of material transfer between the upper and lower mantle are key to Earth’s thermal and chemical evolution. Sinking slabs and rising plumes are generally accepted as locations of transfer, whereas mid-ocean ridges are not typically assumed to play a role. However, tight constraints from in-situ measurements at ridges have proven challenging. We use P-to-S receiver functions to image the mantle transition zone (MTZ) discontinuities using ocean bottom seismic data from the equatorial Mid-Atlantic Ridge (MAR). We image the 660 km discontinuity broadly uplifted by 10 ± 4 km over a ~600 km swath with the 410 km discontinuity depressed by 5 ± 4 km. The thin MTZ is coincident with slow mantle shear wave velocities from global seismic tomography. In addition, MTZ velocities beneath the MAR are on average slower than those beneath older Atlantic seafloor. The observations imply material transfer between the upper and lower mantle, either continuous or punctuated, that is linked to the MAR. Given the length and longevity of the mid-ocean ridge system, it implies whole mantle convection may be more prevalent than previously thought, with ridge upwellings playing a role in counter balancing slab downwellings.